Identification and Characterization of Regulatory Pathways Controlling Dormancy Under Lower Temperature in Alfalfa (Medicago sativa L.) - Liu, Jingfu; Wang, Tiemei; Weng, Yinyin; Liu, Bei; Gao, Qiu; Ji, Wei; Wang, Zhuanling; Wang, Yingwei; Ma, Xiqing (Frontiers in Plant Science, 2022)
Alfalfa (Medicago sativa L.), a kind of high-quality perennial legume forage, is widely distributed in northern regions of China. In recent years, low temperature happens frequently and limits alfalfa productivity and survival in early spring and late fall. However, the underlying molecular mechanisms of alfalfa response to cold tolerance are not well documented. In this study, dormancy and non-dormancy alfalfa standard varieties were characterized under low temperature stress. Our analysis revealed that plant height of dormancy genotype was strongly inhibited by low temperature, flavonoids content and higher expression of flavonoids biosynthesis genes (chalcone synthase, leucoanthocyanidin dioxygenase and flavonoid 3'-monooxygenase) may play essential roles in response to low temperature stress in dormancy genotype alfalfa. Further analyses revealed that receptor-like kinase family genes (including cysteine-rich RLK10, lectin protein kinase and S-locus glycoprotein like kinase), RNA-and-protein synthesis genes (RNA polymerases, ribosomal protein, and protein phosphatase 2C family protein), and proteasome degradation pathway genes (such as F-box family protein, RING/U-box superfamily protein and zinc finger family protein) also highly upregulated and contributed to cold tolerance phenotype in dormancy genotype alfalfa. This will provide new insights into future studies for cold tolerance in alfalfa and offer new target genes for further functional characterization and genetic improvement of alfalfa.